Bibliometric Analysis of Social Media in Government Public Communication Using CiteSpace Software - Raja Abdul Rahim; Achmad Nurmandi; Ridho Al-Hamdi (INJECT (Interdisciplinary Journal of Communication), 2025)
This study aims to analyze the development of social media studies in government public communication using CiteSpace software. The method used in this study is qualitative with a literature review approach. Data sources were obtained from the Scopus database using the keywords “Social Media and Government Public Communication” from 2018 to 2023, resulting in 678 documents related to the research topic. The findings of this study indicate that social media studies as a means of government public communication in 2020 became a trending topic, as evidenced by the number of scientific publications in 2020 being the highest, namely 15 articles. Due to the COVID-19 pandemic, the government conducted a lot of coordination and provided information through social media. The United States contributed the most scientific publications, namely 25 articles. Meanwhile, social sciences were the most researched field related to social media and government public communication. Facebook served as a platform for the government to communicate and provide information regarding the handling and prevention of COVID-19. Meanwhile, Twitter was used by the government to open a dialogue space to receive ideas and input from the public. This study contributes to the government's understanding of how to build effective public communication for the community. This study has limitations in terms of the data sources analyzed, as it only uses data from the Scopus database to examine the development of social media studies as a tool for government public communication.